Enforcing Semantic Integrity on Untrusted Clients in Networked Virtual Environments. - Jha, S; Katzenbeisser, S; Schallhart, C; Veith, H; Chenney, S (IEEE, 2007)
In the computer gaming industry, large-scale simulations of realistic physical environments over the Internet have attained increasing importance. Networked virtual environments (NVEs) are typically based on a client-server architecture where part of the simulation workload is delegated to the clients. This architecture renders the simulation vulnerable to attacks against the semantic integrity of the simulation: malicious clients may attempt to compromise the physical and logical rules governing the simulation, or to alter the causality of events. This paper initiates the systematic study of semantic integrity in NVEs from a security point of view. We present a new provably secure semantic integrity protocol which enables the server system to audit the local computations of the clients on demand. © 2007 IEEE.